Organizing Music Circles Outside the Classroom - kizi, Rustamjonova Dilkhavas Ravshvnbek (Researchparks Publishing, 2023)
In this article, recommendations are given about the activity of conducting music clubs and its importance for students to spend their time outside school productively. Also, the necessary recommendations about the organization of music clubs, their proper conduct, and the form of their organizational structure have been highlighted.